Demonstrate and absence of mediated everyday moments: the public space in Bogotá (2019)
In this paper the relationship between new media and the appropriation of public space is to design artwork is presented. Demostrations public spaces are taken, are present and dazzle the possibilities with new technologies, where light, sound and video are diluted with nature and artificiality of the place, therefore, virtually plotted space, build a new one. likewise, his absence opens up possibilities for the creation of a new intervention, otherwise renovation of space. So, understand public space exploring the world, that is, to recognize what is and how it lives, started question about how everyday life can be transformed by the mediation, while inferences about the re-construction of the public from participation in the art of the people that currently pass those places.